Answer:
pA = 0.095 atm
pB = 0.303 atm
Explanation:
Step 1: the reaction
AB(s) ⇔ A(g) + B(g)
Kp = pA * pB
⇒ with Kp = equilibrium constant
Kp = 0.126 * 0.23 ⇒ Kp = 0.02898
Since the container will be compressed to half of its original volume, means that he pressure will be doubled.
⇒pA = 0.252
⇒pB =0.46
To establish this equilibrium, each pressure has to be lowered by x
⇒pA = 0.252 - x
⇒pB = 0.46 - x
Kp = 0.02898 = (0.252 - x)(0.46-x)
0.02898 = 0.11592 - 0.252x -0.46x + x²
-x² + 0.712x - 0.08694 = 0
D= b² - 4ac
⇒ D = 0.712² -4*(-1) *(-0.08694) = 0.506944 -0.34776 =0.159184
x = (-b ± √D)/2a
x = (-0.712 ± √0.159184)/(2*-1) = (-0.712 ± 0.398978696)/-2
x = 0.156510652 or x= 0.555489348
x = 0.555489348 is impossble or the pressure would be negative
x=0.156510652
pA =0.252 - 0.156510652 = 0.095489348 atm
pB = 0.46 - 0.156510652 = 0.303489348 atm